Analysis of Indigenous and Intercultural Public Education in Mexico - González, Felipe (Tanzania Journal of Sociology, 2025)
This article analyzes the processes of indigenous and intercultural education in Mexico as components for the ideological construction of national identity. An important question arises: why do we Mexicans have so much trouble identifying with our cultural differences? From a historical and contemporary perspective, it is analyzed the articulation between two historical moments: a) The basic level indigenous education, implemented throughout the 20th century and b) The intercultural higher education, which began at the beginning of the 21st century. Although each one has its nuances, they are analyzed as part of a historical continuum that stands as a project that, in its integrative intention, ends up being disruptive and colonial. This work is done with a participant observation methodology as the author was a central actor in the implementation of the intercultural higher education model, so the anecdotes will always be presented to generate reflections and provide elements for the revitalization of cultures and their acceptance within the framework of the national culture of Mexico.The output product of this model it faces a society whose colonialist cultural devices do not value original cultures, subjugating their epistemology and their knowledge.